Review Paper on Tracking and Its Types - Muley, Nayan; Thawari, Pratiksha; Sarangpure, Vaishali (International Journal of Computer Sciences and Engineering, 2015)
Tracking system is used for the observing of persons or objects on the move and it supplying a timely ordered sequence of respective location data to a model. There is different type of tracking. One of the most important tracking is mobile tracking. Mobile phone tracking refers to the ascertaining of the position of a mobile phone. In this paper student information tracking system is the technique in this we are willing to fetch the information about an individual student and pass it to the authenticated user only that individual can see this send information from student device (android phone). This paper provides the communication between several of the users i.e. college, staff, student, company, Employees etc. The information such as the student call logs , browsing history, their current location etc. all with the time stamp are fetch from the devices and pass it to the user specifies such as Parents, teacher and /or any authenticated person.